2021
DOI: 10.1111/jori.12346
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the relation between digitalization and the market value of insurers

Abstract: We analyze the relation between digitalization and the market value of US insurance companies. To create a text‐based measure that captures the extent to which insurers digitalize, we apply an unsupervised machine learning algorithm—Latent Dirichlet Allocation—to their annual reports. We show that an increase in digitalization is associated with an increase in market valuations in the insurance sector. In detail, capital market participants seem to reward digitalization efforts of an insurer in the form of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 69 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…202 On the other hand, Guo et al (2020) found that digitalization can increase firm performance while in crisis situation. Fritzsch et al (2021) found that digitalization can increase market valuation which result on higher market capitalization and market-to-book ratios. Wu et al (2022) has found that digital transformation can minimize the stock price crash risk.…”
Section: Clarissa Dominique Effendi Handajani Yie Ke Feliana Rizky Er...mentioning
confidence: 99%
“…202 On the other hand, Guo et al (2020) found that digitalization can increase firm performance while in crisis situation. Fritzsch et al (2021) found that digitalization can increase market valuation which result on higher market capitalization and market-to-book ratios. Wu et al (2022) has found that digital transformation can minimize the stock price crash risk.…”
Section: Clarissa Dominique Effendi Handajani Yie Ke Feliana Rizky Er...mentioning
confidence: 99%
“…Although many studies have used traditional linear approaches, applying machine learning methods to detect insurance claim fraud has become increasingly popular. Current literature argues that this will play an important role in creating more efficient fraud detection mechanisms (Bauer et al, 2021), which could increase the market value of insurance companies (Fritzsch et al, 2021). Machine learning can be defined as a process in which “a computer observes some data, builds a model based on the data, and uses the model as both a hypothesis about the world and a piece of software that can solve problems” (Russell & Norvig, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies mainly focus on how firms handle operating risks (Gamba & Triantis, 2014), commodity price uncertainty (Haushalter et al, 2002;MacKay & Moeller, 2007), financial market risks, or a combination of all three (Smithson & Simkins, 2005). Moreover, recent studies such as Fritzsch et al (2021) find that introducing digitalization which potentially improves firm risk management practices, is also positively associated with corporate value.…”
Section: Related Literaturementioning
confidence: 99%